The method of calculation of flooding zones on an territory with the use of digital elevation model on the basis of successive pools - Baktybekov, K.; Bekmukhamedov, B.; Muratbekov, M.; Altynbek, S. (Publishing House of the KarSU named after E.A.Buketov, 2015)
An integral part of improving the quality of control and receiving risk assessments is the development of simulation models that predict the possible dynamics of natural disasters in high-risk regions. One of the main factors influencing the pattern of flooding is a relief. In the paper we propose a method of ―successive pools‖ to simulate flood zone area during emergency situations using a digital elevation model. The method allows to hide the non-linearity in natural relationship between the pools and simulate the movement of large flows of water.
Keywords: floods; digital elevation models; calculation of flooding zones